Social entrepreneurship among university students: the Grey Oyster Mushroom Project For Happiness / Hardy Loh Rahim … [et al.] - Rahim, Hardy Loh; Buyong, Siti Zahrah; Mohamed Noah, Roha; Khairani, Noor Sufiawati; Abdullah, Aryani; Tuan Azam, Syed Khusairi; Abu Bakar, Zarina (2018)
The Grey Oyster Mushroom Project for Happiness (GOM) was initiated at Universiti Teknologi MARA (UiTM) with the aims of creating social entrepreneurs among students as well as alleviating poverty and social problems through social entrepreneurship project. The project has chosen the disabled from Community-Based Rehabilitation in Segamat, Johor as the beneficiaries after performing a social and economic needs analysis. As the beneficiaries are suffering from social stigma and unable to be financially independent, GOM Project has given a light of hope for them and able to increase their social and economic livelihood. GOM Project was able to create a sustainable and profitable oyster mushroom business for the beneficiaries, directly impacted 30 disabled persons and 14 students as well as indirectly impacted thousands of people. It was able to fulfill three of Sustainable Development Goals introduced by the United Nations, namely decent work and economic growth, good health and wellbeing as well as reduced inequalities.